ショウワキチ シュウヘン デ サイシュウ サレタ ギョルイ ノ リスト オヨビ ケンサク ヒョウ - 岩見, 哲夫; イワミ, テツオ; 内藤, 靖彦; ナイトウ, ヤスヒコ; Iwami, Tetsuo; Naito, Yasuhiko (1983)
P(論文) 現在まで, 昭和基地周辺より採集報告のある魚種を再検討した結果, 昭和基地周辺には少なくともノトセニア科10種(Trematomus bernacchii, T. hansoni, T. newnesi, T. nicolai, T. loennbergii, T. centronotus, T. scotti, Pagothenia borchgrevinki, Dissostichus mawsoni, Pleuragramma antarcticum), バシドラコ科1種(Gymnodraco acuticeps), ゲンゲ科1種(Austrolycichthys brachycephalus)の計12種の魚類が生息していることが確認された。これら12種の魚類に対する検索表を作製し, 和名の付いていなかった4種について新和名を付けた。 The fishes around Syowa Station are becoming familiar to the expedition participants who fish and observe, and fish collection increased slowly but steadly. But ichthyological study of these fishes is still in a preliminary stage and general biological information is quite scarce while ichthyological works on the fishes of the other parts of the Southern Ocean have observed remarkable advancement since 1972 when the first list of the fishes of Syowa Station was published (ABE and HOSHIAI; Nankyoku Shiryo (Antarct. Rec.), 43,25,1972). It is thought timely to rearrange the information up to date. In the present report is given a list of the species with a key based on new data. Three families, six genera and twelve species are dealt with here : Trematomus bernacchii, Trematomus hansoni, Trematomus newnesi, Trematomus nicolai, Trematomus loennbergii, Trematomus centronotus, Trematomus scotti, Pagothenia borchgrevinki, Dissostichus mawsoni, Pleuragramma antarcticum, Gymnodraco acuticeps, Austrolycichthys brachycephalus. departmental bulletin paper